MISTERI LEMBAH HANTU: HORROR NOVEL AND VIOLENCE IN FAMILY RELATION - Nariswari, Fitria Sis; Yoesoef, M. (UI Scholars Hub, 2019)
The talk on horror stories never ceased to be discussed, as ones will find any topics regarding horror stories, even in daily conversation. The horror stories permeated in Indonesia during the period of 1970-1990s were considered as a third-rate literature, even though it had a considerable amount of readers who were fans of these stories. During the period, Abdullah Harahap came into the spotlight and became the most productive horror writer compared to his colleagues. However, Abdullah Harahap, who were prominent among readers during 1970-1990s, turns to be a less-known writer when it comes to academic research. This research examines Misteri Lembah Hantu (1988), a novel written by an Indonesian writer Abdullah Harahap, that the novel is regarded to sufficiently represent the stories in other novels that exhibit the elements of violence, abnormal sexuality, and the troubled nuclear family relation. The novel be will analyzed from its plot to understand the narrative pattern. Plot and character analysis will be used to comprehend how violence and abnormal sexuality described in Misteri Lembah Hantu (1988). Additionally, a horror story can also show how it is used to confront anomaly, anxiety, and fear which is different compared to the everyday life. Fear and anxiety are impossible to be expressed in the real world, but they can be manifested through a literary work. The violence and abnormal sexuality in Misteri Lembah Hantu also can be concluded as the symbol that improper parenting from the nuclear family will impact the chaos happened in the broader community, for instance the society.